Games for Teaching/Learning Quantum Mechanics: A Pilot Study with High-School Students - Maria Luisa Chiofalo; Caterina Foti; Marisa Michelini; Lorenzo Santi; Alberto Stefanel (MDPI AG, 2022)
The teaching of quantum physics is challenging, not the least because teachers must overcome the traditional narrative approach, students must gain a conceptual understanding of fundamentals, and citizens must become aware of quantum technologies. Quantum games are powerful tools to overcome obstacles and push one's limits without fear of failure. We report on a pilot study involving twenty high-school student volunteers, consisting of a compact intervention module on the concepts of quantum states, properties, measurement, superposition, and entanglement within the framework of the Model of Educational Reconstruction, followed by playing a game, quantum TiqTaqToe. The outcomes of this research-based learning environment are discussed via the qualitative analysis of students' answers to two open questionnaires. We find that students grasped the concepts of superposition and, with special awareness, entanglement, the game proving effective to help students experience their implications in quantum behavior. The informal and stimulating tournament atmosphere favored intertwining of the game with learning goals. Our central message is that the use of quantum game tools fits a teaching/learning environment in manners often not well understood in the literature; it enhances awareness of the nature of new and non-intuitive concepts, increases complementarity with other languages within the process of thinking about physics, boosts student engagement, and improves intervention efficiency and effectiveness.